A new variety of Thismia hexagona Dancak, Hrones, Koblova et Sochor (Thismiaceae) from Sabah, Borneo, Malaysia - Hirokazu Tsukaya; Monica Suleiman; Hiroshi Okada (Japanese Society for Plant Systematics, 2014)
Thismia hexagona Dančák, Hroneš, Koblová et Sochor was recently reported from Brunei Darussalam. It is characterized by its unique yellow and brown coloration and sharply hexagonal flower annulus. Here, we also report its discovery during a botanical expedition in the Maliau Basin Conservation Area, Sabah, Borneo, Malaysia. The Malaysian individuals differ from the original description of T. hexagona in the opening angle and size of the perianth lobes. We therefore propose it as a new variety, T. hexagona var. grandiflora Tsukaya, M. Suleiman & H. Okada var. nov. Detailed morphological characters are provided.